Peran Akuntansi Manajemen dalam Meningkatkan Kinerja Keuangan Perusahaan Ritel di Indonesia - Ronald Rose Yangcen; Sri Arliani Zendrato; Aprida Situmorang; Masry Sinaga; Kevin Carlo (Universitas Katolik Widya Karya Malang, 2024)
Management accounting plays a key role in improving the financial performance of retail companies in Indonesia. By using accurate and relevant financial data, management accounting helps management make effective strategic decisions. In the context of retail companies, management accounting helps in optimizing operational costs, planning budgets, and measuring organizational performance. In this research, we will explore the role of management accounting in improving the financial performance of retail companies in Indonesia.